Traditional Game-Based Learning Innovation to Develop Social Skills of Elementary School Students - Rosmaria Rosmaria; Nurul Fadhilah (Ludi Litterarri, 2024)
Traditional games have an important role in developing social skills of elementary school students through interactive and fun learning. In the context of modern education influenced by the development of digital technology, traditional games offer a solution to overcome the decline in children's social interaction. This research explores the application of traditional games as learning media to improve students' communication, cooperation and empathy skills. Through observations, interviews and document analysis, it was found that games such as congklak, engklek and galah asin not only teach moral values such as honesty and responsibility, but also introduce students to the rich local culture. Despite challenges such as limited facilities and teachers' lack of understanding, creative solutions such as training and technology integration can support the implementation of these methods. The results show that traditional games help students build self-confidence, think critically and strengthen social relationships. In addition to being an educational tool, these games are also a means of cultural preservation that is relevant in the midst of globalization. Collaboration between teachers, parents and communities is needed to ensure the sustainability of traditional games in education. With the right approach, traditional games can be an innovative learning alternative that supports students' holistic development.